Speaker’s variabilities, technology and language issues that affect automatic speech and speaker recognition systems - Abushariah, Mohammad A. M.; Zainuddin, Roziati; Alqudah, Assal Ali Mustafa; Khalifa, Othman Omran (IIUM Press, 2011)
Automatic Speech Recognition (ASR) is gammg its importance due to the vast growth generally in technology and computing in specific. From industrial perspective, computers, laptops, and mobile devices nowadays have the ASR support embedded into the operating system. From academia on the other hand, there are many research efforts being conducted addressing this technology in order to contribute to its state-of-the-art. On the other hand, speaker recognition systems are also growing due to various threats, therefore, these systems are mostly meant for security purposes